SOSOK DAN SEPAK TERJANG TOKOH EGENDARIS LA KOKULI MELALUI ANALISIS SIMBOLIK TERHADAP GELARNYA: KAMBERA KAKUNI - Aderlaepe . (Universitas Halu Oleo, 2019)
This research investigates a mysterious figure and his roles in the society of Siua Liwuno ‘nine villages’, a territorial of Munanese kingdom long ago. He was La Kokuli, lived in Watuputih villages and his social tittle was Kambera Kakuni ‘yellow butterfly’. His social tittle is a gate to analyze who was he and what was his roles in the society since there is no written reference about him as the impact of Munanese people as an illiterate society long ago. Through semioticly analysis, he was a sufi ‘islamic metaphysicsm’ who acquainted Islam in the society of siua liwuno ‘nine villages’ Muna in the 17 century. Kambera Kakuni ‘yellow butterfly’ is a symbol of Tarekat Naksabandiah, one of Islam metaphysic doctrin. He came from Aceh, as the pupil of Syech Abdul Rauf Singkil (Syech Tengku Syiah Kuala).